Reflection of "otherness" in international relations - Kvašňák, Daniel; Rolenc, Jan Martin, 1980-; Doležal, Tomáš; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2016)
The current migration crisis has put significant strain on the European Union and its member states. Immigration has always been a contentious issue in societies, most often facing significant opposition. By drawing on postmodern theories of international relations and Discourse Theory, this paper analyses how immigration is being increasingly securitized by the European Union and its member states along with what makes securitization the hegemonic discourse. This is done primarily with reference to identity construction through the framing of the Other, in this case the migrant, as an unwanted and externalized element. Furthermore, the paper details how the framing of the migrant as a threat to the internal security of a country strenghtend identity politics across Europe. Finally, using the Brexit campaign in the UK, the paper analyzes how the rise in identity politics in turn raises the possibility of a successful fusion of the anti-immigration discourse with the anti-EU discourse through the exploiting of societal unease.
Vedoucí práce: Jan Martin Rolenc
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor dipl. práce]; diplomové práce; master's theses